2023
DOI: 10.1186/s13018-023-04265-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with an increased risk of osteochondral injuries after patellar dislocations: a systematic review

Zhi Yi,
Xiaohui Zhang,
Meng Wu
et al.

Abstract: Purpose The purpose of the study was to summarize the available evidence and identify risk factors for osteochondral injuries (OCIs) after patellar dislocations. Methods A systematic literature review was conducted in PubMed, Embase, Web of Science, Cochrane Library, and China national knowledge infrastructure from inception to December 22, 2022, according to the preferred reporting items for systematic reviews and meta-analyses guidelines. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…found that male sex was a risk factor for osteochondral injuries after PD. 14 , 27 Retzky et al . 28 also found that male sex was an independent risk factor for OCF after PD in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that male sex was a risk factor for osteochondral injuries after PD. 14 , 27 Retzky et al . 28 also found that male sex was an independent risk factor for OCF after PD in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bone maturity is not only a risk factor for recurrent patellar dislocation, but it also increases the risk of OCF after PD. 27 , 32 , 33 Flachsmann et al . 34 found that uncalcified cartilage in skeletally immature patients weaves with subchondral bone, which may lead to the adolescent joint particularly susceptible to osteochondral shear fracture.…”
Section: Discussionmentioning
confidence: 99%